The transformation of macrophyte‐derived organic matter to methane relates to plant water and nutrient contents - Grasset, Charlotte (Limnol Oceanogr, 2019)
Macrophyte detritus is one of the main sources of organic carbon (OC) in inland waters, and it is potentially available for methane (CH(4)) production in anoxic bottom waters and sediments. However, the transformation of macrophyte‐derived OC into CH(4) has not been studied systematically, thus its extent and relationship with macrophyte characteristics remains uncertain. We performed decomposition experiments of macrophyte detritus from 10 different species at anoxic conditions, in presence and absence of a freshwater sediment, in order to relate the extent and rate of CH(4) production to the detritus water content, C/N and C/P ratios. A significant fraction of the macrophyte OC was transformed to CH(4) (mean = 7.9%; range = 0–15.0%) during the 59‐d incubation, and the mean total C loss to CO(2) and CH(4) was 17.3% (range = 1.3–32.7%). The transformation efficiency of macrophyte OC to CH(4) was significantly and positively related to the macrophyte water content, and negatively to its C/N and C/P ratios. The presence of sediment increased the transformation efficiency to CH(4) from an average of 4.0% (without sediment) to 11.8%, possibly due to physicochemical conditions favorable for CH(4) production (low redox potential, buffered pH) or because sediment particles facilitate biofilm formation. The relationship between macrophyte characteristics and CH(4) production can be used by future studies to model CH(4) emission in systems colonized by macrophytes. Furthermore, this study highlights that the extent to which macrophyte detritus is mixed with sediment also affects CH(4) production.